2005
DOI: 10.1074/jbc.m503230200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Hairpin-Duplex Conversion for the HIV-1 Dimerization Initiation Site

Abstract: We have used the dimerization initiation site of HIV-1 genomic RNA as a model to investigate hairpin-duplex interconversion with a combination of fluorescence, UV melting, gel electrophoresis, and x-ray crystallographic techniques. Fluorescence studies with molecular beacons and crystallization experiments with 23-nucleotide dimerization initiation site fragments showed that the ratio of hairpin to duplex formed after annealing in water essentially depends on RNA concentration and not on cooling kinetics. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 53 publications
3
46
0
Order By: Relevance
“…Although not as favorable energetically as the formation of Watson-Crick base pairs, C⅐T, C⅐A, and G⅐T pairs (43)(44) can form between the (CAG) 10 and modified (CTG) 10 hairpins. As a third possibility, others have suggested that hairpin melting may occur prior to duplex conversion (25); in this scenario, the unstructured sequences would then anneal to form duplex. However, as monitored by optical methods, for all the hairpin pairs utilized in our experiments the temperature at which duplex formation occurs is well below the T m of the individual hairpins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not as favorable energetically as the formation of Watson-Crick base pairs, C⅐T, C⅐A, and G⅐T pairs (43)(44) can form between the (CAG) 10 and modified (CTG) 10 hairpins. As a third possibility, others have suggested that hairpin melting may occur prior to duplex conversion (25); in this scenario, the unstructured sequences would then anneal to form duplex. However, as monitored by optical methods, for all the hairpin pairs utilized in our experiments the temperature at which duplex formation occurs is well below the T m of the individual hairpins.…”
Section: Discussionmentioning
confidence: 99%
“…Similar methodology has been employed effectively to characterize the folded structures adopted by nucleic acids, including guanine quadruplexes (35), duplex and triplex DNA (36), and hairpin DNA (37) and RNA (25). In this work, we designed the FL-(CAG) 10 -DCL molecular beacon to selectively monitor the behavior of the (CAG) 10 hairpin in the presence of the complementary sequence.…”
Section: Discussionmentioning
confidence: 99%
“…2; 3; 7; 18-20 Experiments performed in vitro have shown that the metastable KL complex can subsequently isomerize into a more stable extended duplex (ED) that involves extensive intermolecular base-pairing along the entire SL1 sequence (Scheme 1). [21][22][23][24][25] The transition between KL and ED forms is catalyzed in vitro by NC, 23; 26-29 in a process that could explain the increased thermal stability observed for genomic RNA of HIV-1 and Moloney murine leukemia virus upon protease-dependent viral maturation. 30-32 The 3D structures of SL1 constructs in monomeric, 33-35 KL, 36-40 and ED form 38; 41-43 support the two-step dimerization model.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, hyperchromicity and the shape of the melting profiles provided further hints as to the (co)existence of hairpin and duplex secondary structures in solution. We are aware that for the quantification of hairpin/duplex ratios, other methods such as gel-shift assays under native conditions (Bernacchi et al 2005Ennifar et al 2007;Sun et al 2007) or NMR spectroscopy are required (Micura et al 2001). Here, the set of RNAs was exclusively investigated by UV absorbance/temperature profiles.…”
Section: Resultsmentioning
confidence: 99%